The Challenges Encountered by the Unvaccinated Employees of Barangay Nagkaisang Nayon, Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the challenges encountered by unvaccinated employees in BarangayNagkaisang Nayon, Novaliches, Quezon City. The purpose of this study was to determine thechallenges encountered by unvaccinated employees and to assist them through proposedrecommendations and solutions to overcome and minimize the problems and challenges thatthey are facing. Purposive sampling was conducted at Barangay Nagkaisang Nayon inNovaliches, Quezon City. Survey questionnaires were used in the quantitative researchdesign. It was determined that the challenges that unvaccinated employees encounter aretheir fear of being vaccinated because of the possible side effects that they might experienceand their belief that getting the COVID-19 vaccine would cause infertility in female employees.Transportation and discrimination were also some of the challenges that unvaccinatedemployees faced since they were not allowed to ride public transportation without presenting avaccination card. In terms of discrimination at their workplace, it is visible that there is unfairtreatment between vaccinated and unvaccinated employees and that with the help ofproposed recommendations and solutions, the challenges that unvaccinated employeesencounter could be minimized.Results showed that the reasons for being unvaccinated were in terms of Fear of BeingVaccinated. Results showed that some unvaccinated respondents are afraid of gettingvaccinated because they are worried about the possible side effects. Vaccine Allergy – resultsshowed that the respondents to the study strongly agreed that employees who are allergic toany type of vaccine or injectable medication must first consult with their doctors before gettingvaccinated. Pregnancy Issues – most of the respondents believed that getting vaccinatedwhile pregnant would result in infertility. The results showed the challenges encountered bythe unvaccinated respondents in terms of transportation. Results showed that therespondents to the study strongly agreed that employees who have not been immunized arenot allowed to use public transit. Discrimination – results showed that some of therespondents strongly agreed that several employees said they were limited in their travelaround the office, while others were laid off. And, Work Environment – the respondentsstrongly agreed that there is unfair treatment between vaccinated and unvaccinatedemployees at their workplace. The proposed solutions for the challenges encountered by theunvaccinated respondents addressed the challenges and encouraged not only theunvaccinated employees but also their coworkers and employers to minimize and avoidpossible future challenges. The results of the present study strongly confirm that there areseveral challenges faced by unvaccinated employees.The researchers advised unvaccinated employees, employers, and their coworkers to strictlyfollow the COVID-19 rules and regulations to avoid contracting and transmitting the virus. The researchers also recommend that employers educate and inform their employees about theCOVID-19 virus and vaccinations. The employees who received discrimination and judgmentsfrom their coworkers should be ignored, and the researchers recommend that they focus onimproving their performance at work. Unvaccinated employees should always be aware oftheir surroundings and the people they encounter, and they should always wear a facemask.
Keywords: Health services management